2013
DOI: 10.1097/mej.0b013e328356f754
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of emergency physician-performed ultrasound in detecting traumatic pneumothorax after a 2-h training course

Abstract: After just a 2-h training course, emergency physicians showed a good success rate in finding pneumothoraces. Thoracic US can be an easy to learn and an accurate diagnostic modality for the detection of traumatic pneumothorax in emergency departments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 17 publications
1
39
0
1
Order By: Relevance
“…We feel this is not significant enough to withhold this simple, rapid and potentially lifesaving investigation from those with indications even though they are haemodynamically normal. eFAST lacks sensitivity and specificity of Direct peritoneal lavage (DPL) and accuracy of CT (7). Missing of two small bowel lacerations would not have happened with DPL and CT would have diagnosed the patient with retroperitoneal haematoma in our study and negative laparotomy could have been avoided.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We feel this is not significant enough to withhold this simple, rapid and potentially lifesaving investigation from those with indications even though they are haemodynamically normal. eFAST lacks sensitivity and specificity of Direct peritoneal lavage (DPL) and accuracy of CT (7). Missing of two small bowel lacerations would not have happened with DPL and CT would have diagnosed the patient with retroperitoneal haematoma in our study and negative laparotomy could have been avoided.…”
Section: Discussionmentioning
confidence: 99%
“…Pneumothorax is one of the leading causes of preventable trauma deaths. In a study in 2013 involving 153 patients Abbasi et al showed eFAST to have sensitivity, specificity, positive predicting value and negative predictor value of 86.4%, 100%, 100% and 95.6% respectively in diagnosing pneumothorax (7). Corresponding values for Chest X ray was lower at 48.6%, 100%, 100% and 85.1%.…”
Section: Discussionmentioning
confidence: 99%
“…[17,19,20] In the study of Mao et al, the average duration of US has been 2.3±2.9 min., APCR 12.4±6.7 min. and chest CT 16.3±7.8 min.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that a directed 1-day ultrasound-based training course is sufficient to equip the non-radiologist clinician with the necessary skill in evaluating limited anatomy of interest. [35][36] A limitation to our study is that individuals with facial distortion, previous mandibular surgery/trauma or missing teeth between the lower first molars were excluded. Perhaps, the mental foramen may have been subject to distortion or shift and hence difficult to visualize in these patients.…”
Section: Discussionmentioning
confidence: 99%